154k views
5 votes
Simplify 3j - {2k - [5h - (3j + k)]}.

User Cumhur Ata
by
4.6k points

2 Answers

4 votes

Answer:

5h-3k

Explanation:

User Corbin Tarrant
by
5.7k points
5 votes

Hey there!!

Remember PEDMAS ?

P = parenthesis

E = exponents

D = division

M = multiplication

A = addition

S = subtraction

THE ORDER OF BRACKETS -

( ) - solved first

[ } - solved second

{ } - solved third

Now, according to PEDMAS , we will need to solve the brackets first

3j - { 2k - [ 5h - ( 3j + k )]}

3j - { 2k - [ 5h - 3j - k ]}

3j - { 2k - 5h + 3j + k ]

3j - { 3k - 5h + 3j }

3j - 3k + 5h - 3j

5h - 3k is the final answer

Hope my answer helps!

User Brigo
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.